La evolución de los medios de comunicación digitales y su impacto en la competitividad: Un análisis de estrategias y tendencias emergentes. - Briones Tapia Armando David (2024)
The research has been carried out considering the evolution of digital media and its impact on competitiveness: An analysis of strategies and emerging trends, where it was identified that in recent years there has been a growth in digital media that use the digital platform of Facebook or YouTube, which has allowed journalism professionals to find an alternative to work in their profession, although they do so informally, these digital media have quite a reach with thousands, hundreds of thousands and millions of reproductions of their videos, which allows them to monetize on digital platforms, and thanks to the audience, receive advertising from companies and ventures that hire them to promote their products or brands. Through a mixed research, non-experimental design, descriptive, documentary and applied, with the use of survey and interview techniques, instruments have been applied to obtain primary information from the study population. The hypothesis was validated with the Chi Square statistical test: The evolution of digital media has a positive impact on business competitiveness. The design of a content grid for a digital communication medium that allows the integration of communities has been proposed. In conclusion, digital media have high levels of acceptance by users of social networks, which allows them to receive advertising to very successfully promote different brands or products, requiring improvement of their content to retain their audience by offering a varied programming.